28 Days Sub Acute Toxicity Studies of the Methanol Stem Bark Extract of Combretum hypopilinum Diels (Combretacea) in Rats - Abubakar Kabiru , Usman Aminu , Yerima Musa , Muhammad Abubakar Amali , Samaila Hassan , Abdullahi 1 1 Suleiman , Rabiu Tijani Giaze and Milicent Ladi Umaru (Sokoto Journal of Medical Laboratory Science)
The aim of this study was to evaluate the safety profile of Combretum hypopilinum stem bark extracted with Methanol (70%v/v). Preliminary Phytochemical screening of the crude methanol stem bark extract was carried out, and revealed the presence of secondary metabolites such as steroids, flavonoids and alkaloids. Initial oral acute toxicity test was carried out using the Limit Dose Test to ascertain the safety of the extract in rats. Sub-acute toxicity testing was conducted by 28 days oral administration of 400 mg/kg, 800 mg/kg and 1600 mg/kg body weight to three groups of ten rats. The fourth group was administered distilled water 10 ml/kg. No major changes were observed in body weight of the animals following 28 days of daily oral administration. Biochemical parameters such as Total Protein, Total Bilirubin, Creatinine, Aspartate Transaminase (AST) and Alanine Transaminase (ALT), were found to be within normal ranges. The levels of marker enzymes in the vital organs did not show any significant changes between control and treated groups. Histopathological examination of the major vital organs (liver, brain, and kidney) revealed no significant pathological changes in the treated groups of rats. The results of the present work suggested that the methanol stem bark extract of Combretum hypopilinum is relatively safe for use at the tested doses.